Prison Riots in Britain and the USA, 2nd ed - Adams, R. author. aut Link
XIV, 294 p.
Keywords: 'This is among the handful of prison books - they include George Jackson's Soledad Brother and BB Michael Ignatieff's A Just Measure of Pain - which moves and informs. The sociology of prison riots,MM the causes of outbreak and the nature of the reactions, are subjects which have been largely ignored and need to be understood by those who either study criminal justice or work in the system.' - His Honour Judge Stephen Tumin This challenging book is essential reading for everyone with an interest in penal policy and practice. It uses extensive documentary evidence to demonstrate that prison riots in Britain and the US have shifted from traditional riots in which prisoners made no specific demands, to consciousness-raising riots where they often challenged the dominant penal philosophy of rehabilitation. The book illustrates the violent nature both of many prison riots and of responses to them by the authorities. It concludes that the challenge to all involved in debates about penal policy and practice is to project a future for prisons which goes beyond the patterns of confrontation which have been so much a feature of prison riots in the past.